THE POTENTIAL OF ROMANIAN WINERIES IN WINE TOURISM DEVELOPMENT - Andra - Elena GURGU; Gina FÎNTÎNERU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Wine tourism in Romania is relatively a new concept that became a topic of interestin the last years. If countries such as France, Italy, Spain or Australia are already well known not only for their wine quality, but also for diverse wine tourism activities that are taking place in their most known wine regions, Romania is stillin progress with wine tourism development.The aim of this paper is to highlight the wine-growing and wine-making potential of Romania and the way it could leadto the growth of the wine tourism. From the quantitative analysis that was made in order to see where the country stands in terms of wine production, exports, imports and consumption compared with the main wine producing countries,it has been seen that Romania has a positive evolution trendandoverall, it ranks 13th worldwide in regard to wine production.Additionally, the second part of the analysis has shown the classification of Romanian wine regionsand the number of wineries per region, as well as the main wineries that offer wine tourism services. Considering the dimension of the wine sector, there is an orientation of Romanian wineries towards the growth of the wine tourism services, where currently Muntenia and Oltenia wine regions stand out.